A modified perioperative regimen for deceased donor kidney transplantation in presensitized recipients without prior desensitization therapy - Guo, Zhiliang; Zhao, Daqiang; Sa, Rula; Wang, Lu; Li, Songxia; Zhao, Guangyuan; Zhu, Lan; Chen, Gang (Frontiers in Immunology, 2023)
Backgrounds: Renal transplantation in HLA-presensitized recipients entails an increased risk of antibody-mediated rejection (AMR) and graft loss. There is currently no accepted standard treatment protocol that can help transplant surgeons safely perform deceased donor (DD) kidney transplantation in presensitized patients without pretransplant desensitization. Methods: Fifty-one panel-reactive antibody (PRA)-positive recipients and 62 PRA-negative retransplant recipients (control) who received DD renal transplantation were included. Patients in the presensitized group (donor-specific antibody [DSA]-positive, n=25; DSAnegative, n=26) without desensitization received a modified perioperative treatment starting on day 0 or -1 with rituximab, thymoglobulin, and low daily doses of intravenous immunoglobulin (IVIG, 10-20 g/d, for 14 days). Plasmapheresis was performed once before surgery in DSA-positive recipients. Results: The median follow-up time was 51 months in the presensitized group and 41 months in the control group. The incidence of early acute rejection (AR) and AMR (including mixed rejection) was 35.3% and 13.7% in the presensitized group, respectively, significantly higher than in the control group (14.5% and 1.6%, respectively). Within the presensitized group, the DSA-positive subgroup had more AMR than the DSA-negative subgroup (24.0% vs. 3.8%), but the incidence of T cell-mediated rejection was comparable (20.0% vs. 23.4%). In the presensitized group, all rejections were successfully reversed, and graft function remained stable during follow-up. The 1-year and 3-year survival rates of the grafts and recipients in this group were 98.0%. Conclusions: With a modified IVIG-based perioperative regimen, excellent intermediateterm graft and recipient survival outcomes can be achieved in presensitized patients who received DD kidney transplantation without prior desensitization.